(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Benmark Holding Incorporation is a food and non-establishment company located on the 20th floor of Skysuites Tower Quezon Ave., Quezon City. The company is currently having difficulties in having social responsibilities for its employees. The researchers recommend a proposed development plan for the company to enhance employees’ social responsibilities. Being socially responsible includes having corporate ethics rules that enhance an organization’s social, economic, and environmental performance. By exercising social responsibility, businesses can control their impact on society and the actions that are helpful to society. Through a range of environmental and social efforts, the socially responsible business demonstrates its commitment to having a beneficial impact on society and communities. To benefit employees and society and promote the use of sustainable business practices in economics, a corporation should take social responsibility. Being socially conscious can give a business a competitive advantage. Based on the assessment of economics, the married respondents strongly agree with 4.4, and single respondents very strongly agree with 4.5, which talks about how increasing employee performance might increase trust. The married respondents strongly agree with 4.4, and single respondents very strongly agree with 4.5 in the assessment of social maintaining relationships built by every employee. Lastly, in the assessment of the environment, the married respondents very strongly agree with 4.5, and single respondents strongly agree with 4.4, which is the effect of the condition of the workplace on the work efficiency and loyalty of employees in a company. The researcher makes conclusions and recommendations for improving the social practices within a company. According to the research findings, the company has ineffective training methods, performance problems, lack of direction in their roles, conflict management, and lack of opportunity for growth, which are the most common problems that employees encounter. The researchers proposed a development plan for the employees of Benmark Holding Incorporation. The following are suggested: enhance their social interaction, conduct regular team building, social activity, and seminars, recognize the hard work of employees, and employees should do more often in a field to know more about their goals.